Risk of Future Maltreatment: Examining Whether Worker Characteristics Predict Their Perception. (November 2022) - Lwin, Kristen; Filippelli, Joanne; Fallon, Barbara; King, Jason; Trocmé, Nico
Child welfare workers aim to promote the well-being and safety of children and are the link between the child welfare system and families. Families served by the child welfare system should expect similar service based on clinical factors, not based on their caseworker's characteristics. Using secondary data analyses of the most recent Canadian Incidence Study of Reported Child Abuse and Neglect (CIS-2008) and multilevel modeling, this study examines whether child welfare worker characteristics, such as education level and field, age, and experience predict their perception of the risk of future maltreatment. A total of 1729 case-level investigations and 419 child welfare workers were included in this study. Several one-level logistic regression and two-level logistic regression analyses were run. The best-fit model suggests that caseworkers with a Master's degree, more than 2 years of experience, and more than 18 cases were significantly more likely to perceive risk of future maltreatment. Further, the interaction between degree level and age also significantly predicted the perception of risk of future maltreatment. Results suggest that the perception of risk of future maltreatment may be influenced by caseworker factors, thus service to families may differ based on caseworker characteristics.